2013
DOI: 10.1017/jfm.2013.473
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent acidic jets and plumes injected into an alkaline environment

Abstract: The characteristics of an acidic turbulent jet and plume injected into an alkaline environment are examined theoretically and experimentally. Fluid-flow and chemistry models are combined to understand how the concentration of acid in a parcel of fluid changes as it reacts with alkaline fluid entrained from the ambient. The resulting model is tested in an experimental study in which nitric acid jets or plumes are injected into a large tank containing a variety of alkaline substances. A video camera records a pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The thermal only turned completely yellow when all of its volume had mixed and reacted. In turbulent plumes with instantaneous chemical reaction (Ülpre, Eames & Greig 2013), the presence of reacted and unreacted parcels within the plume has also been observed in the laboratory but was not commented upon by the authors. The unmixed blue parcels of the thermal here, where reaction is yet to occur, appear distributed throughout the whole thermal and strongly affect chemical conversion.…”
Section: Comparison Of Experimental Results With the Theorymentioning
confidence: 98%
“…The thermal only turned completely yellow when all of its volume had mixed and reacted. In turbulent plumes with instantaneous chemical reaction (Ülpre, Eames & Greig 2013), the presence of reacted and unreacted parcels within the plume has also been observed in the laboratory but was not commented upon by the authors. The unmixed blue parcels of the thermal here, where reaction is yet to occur, appear distributed throughout the whole thermal and strongly affect chemical conversion.…”
Section: Comparison Of Experimental Results With the Theorymentioning
confidence: 98%
“…Theoretical and numerical analysis was conducted to comply with the regulation on the scrubber wash water discharge from ships. In the theoretical chemical models, the pH was calculated based on the initial pH and dilution ratio [9,17]. The volume fraction at 4 m from the discharge point was calculated through dispersion analysis of the turbulent jet flow.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, modeling was based on the acid-weak alkali reaction reported in the works of Ülpre et al [9] and Ülpre [17]. These chemical reactions are detailed in said references.…”
Section: Chemistry Reactionmentioning
confidence: 99%
See 2 more Smart Citations